2018
DOI: 10.1111/1365-2664.13122
|View full text |Cite
|
Sign up to set email alerts
|

Grower and regulator conflict in management of the citrus disease Huanglongbing in Brazil: A modelling study

Abstract: In managing plant diseases, there is often tension between a regulator seeking to destroy infected plants to prevent further infection on a national scale and growers seeking to retain infected plants to continue obtaining yield. A high‐profile example is Huanglongbing (HLB) or citrus greening, a bacterial disease that threatens Brazil's citrus industry. To prevent the spread of HLB, especially from abandoned infected groves, the government regulated that if 28% of a plantation unit (grove) is found to be symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…B 374: 20180281 these general features in strategic epidemiological models, for the benefit of future decision-makers facing the same challenges. Good progress in this kind of integrative work has already been made [21,24,[36][37][38][39][40]. A significant challenge faced by epidemiology is to integrate the valuable insights these analyses provide with close programme support work of the type described here.…”
Section: Discussionmentioning
confidence: 94%
“…B 374: 20180281 these general features in strategic epidemiological models, for the benefit of future decision-makers facing the same challenges. Good progress in this kind of integrative work has already been made [21,24,[36][37][38][39][40]. A significant challenge faced by epidemiology is to integrate the valuable insights these analyses provide with close programme support work of the type described here.…”
Section: Discussionmentioning
confidence: 94%
“…Poorly designed disease management strategies can 180 lead to expensive failures of control, as was the case for control of Dutch elm disease in the UK [33] and citrus 181 canker in Florida [34]. Although detailed simulation models have been used to optimise management strategies for 182 a number of plant pathogens [3,32,[35][36][37][38][39][40][41], computational constraints mean that strategies under test are typically 183 restricted to one from a small set of possibilities in which the amount of control remains constant over time. Here we 184 have shown how frameworks for using optimal control theory [9] can be applied to realistic simulation models to 185 understand a practical disease management question, and identify effective management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Management of the isolated outbreak in Oregon has been effective at slowing the spread, containing 38 the disease within Curry county [4]. In some locations, control in Oregon has shown that local eradication, whilst 39 difficult, is possible [5]. Mathematical models however, have had little to say about how this local control should be 40 optimised.…”
Section: Introductionmentioning
confidence: 99%
“…These simulation models accurately capture the dynamics of the real system and so have become important tools for assessing policy decisions relating to real-time management responses as well as to increased preparedness for future threats. Examples include vaccination policies for human papillomavirus in the UK [5,6], livestock culling policies [7,8] and vaccination optimization [9,10] for footand-mouth disease, and optimal host removal strategies for tree diseases of citrus [11][12][13][14] and sudden oak death [15].…”
Section: (A) Realistic Simulation Modelsmentioning
confidence: 99%